Application of aqueous two-phase micellar system to improve extraction of adenoviral particles from cell lysate - Dutra Molino, Joao Vitor; Lopes, Andre Moreni [UNESP]; Viana Marques, Daniela de Araujo; Mazzola, Priscila Gava; Silva, Joas Lucas da; Hirata, Mario Hiroyuki; Crespo Hirata, Rosario Dominguez; Viccari Gatti, Maria Silvia; Pessoa, Adalberto (Wiley-Blackwell, 2018)
Viral vectors are important in medical approaches, such as disease prevention and gene therapy, and their production depends on efficient prepurification steps. In the present study, an aqueous two-phase micellar system (ATPMS) was evaluated to extract human adenovirus type 5 particles from a cell lysate. Adenovirus was cultured in human embryonic kidney 293 (HEK-293) cells to a concentration of 1.4 x 10(10) particles/mL. Cells were lysed, and the system formed by direct addition of Triton X-114 in a 2(3) full factorial design with center points. The systems were formed with Triton X-114 at a final concentration of 1.0, 6.0, and 11.0% (w/w), cell lysate pH of 6.0, 6.5, and 7.0, and incubation temperatures at 33, 35, and 37 degrees C. Adenovirus particles recovered from partition phases were measured by qPCR. The best system condition was with 11.0% (w/w) of Triton X-114, a cell lysate pH of 7.0, and an incubation temperature at 33 degrees C, yielding 3.51 x 10(10) adenovirus particles/mL, which increased the initial adenovirus particles concentration by 2.3-fold, purifying it by 2.2-fold from the cell lysate, and removing cell debris. In conclusion, these results demonstrated that the use of an aqueous two-phase micellar system in the early steps of downstream processing could improve viral particle extraction from cultured cells while integrating clarification, concentration, and prepurification steps.
Keywords: adenovirus particles; aqueous two-phase micellar system; clarification; partitioning of viral particles; preconcentration